Impact of emotional intelligence on teacher's performance in higher education institutions of Pakistan - Muhammad Asrar-ul-Haq; Sadia Anwar; Misbah Hassan (Future Business Journal, 2017)
This research paper aims at investigating the impact of emotional intelligence on teacher's job performance in the education sector of Pakistan. Sample size consists of 166 teachers from universities in the area of central Punjab, Pakistan. Theories of emotional intelligence proposed by Salovey and Mayer (1989-1990) were used as the conceptual framework and its relationship with the job performance of teachers was examined. Reliability and validity of variables was tested through measurement model of PLS-SEM. The result indicated that emotional intelligence has a significant impact on the teacher's job performance. Key research finding revealed that emotional self-awareness, self-confidence, achievement, developing others and conflict management have a positive and significant relationship with the teacher׳s job performance.
Keywords: 650; Emotional intelligence; Pakistan; Performance; Teachers